Evaluation of drilled hole quality in Al 2024 alloy - KURT, MUSTAFA; KAYNAK, YUSUF (SPRINGER LONDON LTD, 2008)
This paper deals with experimental investigation in the role of different coating, point angle, cutting parameters (cutting speed and feed rate) on the hole quality (hole size, surface roughness, roundness and radial deviation of produced hole) in drilling of Al 2024 alloy. The parameters of hole quality are analyzed under varying cutting speeds (30, 45 and 60 m/min), feed rates (0.15,0.20 and 0.25 mm/rev), depths of cut (2, 15 and 25 mm) and drills (uncoated point angle:118 degrees, TiN Pa:118 degrees, TiAlN Pa:118 degrees, Co 5% Pa:130 degrees, TiN Pa:130 degrees). This study includes dry drilling with 10 mm HSS drills with an axial depth of cut of 30 mm. This study indicate that results of the radial deviations show a similar tendency with the hole size. Hence, it can also be concluded from the experimental results that the radial deviations are effected tool vibrations during drilling. The results of this work show that cutting parameters and coatings have different effects on hole quality. However, when dry drilling aluminum alloys, HSS Co 5% drills show good performance compared to an uncoated, TiN and TiAlN coated drills. Besides, effective results have been obtained using low cutting speed and feed rate. Additionally, the best hole quality obtains from near the bottom of the produced hole.
Keywords: aluminum alloy; dry drilling; hole quality; cutting parameters; radial deviation; ALUMINUM-ALLOYS; CUTTING EDGES; DRY; WEAR; PERFORMANCE; VIBRATIONS; COATINGS; DOMAIN; SPEED; TOOL